A study on the preference of the Institute of Library and Information Science students in the use of subject directories and search engines as search tools in finding e-journal articles in the internet - Del Mundo, Rafael Joseph C.; Reside, Marie Desiree H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study sought to 1.) determine the preference of ILIS Undergraduate and Graduate students in the use of the subject directory and web search engines as search tools in finding e-journal articles in the Internet, based on the advantages, disadvantages, special features of the two search tools; 2.) determine the preferences of ILIS students on the two search tools based on the "Principle of Least Effort"; 3.) see the difference in the preference of Undergraduate and Graduate students in the two search tools. The preferences were established through the use of the survey questionnaire answered by the respondents. Stratified sampling was used to form the sample for ILIS undergraduate graduate students. The results showed that ILIS undergraduate students chose the web search engine over the subject directory. In the case of the ILIS graduate students, their preference on the two search tools was almost equally divided. Based on the advantages (reliability and scope and accuracy of search) and the "Principle of Least Effort, the preference of ILIS graduates students inclined towards the subject directory. While based on the advantages (easiness of search and flexibility of the tools), the disadvantages, and special features, the preference leaned towards the web engine. It is recommended that 1.)topics on the web search tools should be incorporated in the LIS 160 subject (Information Handling and Processing); 2.) future researchers should consider doing an in-depth study of the preference on the two search tools based on hands-on experience of users on the search tools and not just merely providing descriptive information on the tools to determine the preference.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science -- Students; Internet searching -- Philippines -- Quezon City